Indian Red Jungle fowl reveals a genetic relationship with South East Asian Red Jungle fowl and Indian native chicken breeds as evidenced through whole mitochondrial genome sequences - Kanakachari, M.; Chatterjee, R. N.; Reddy, M. R.; Dange, M.; Bhattacharya, T. K. (Frontiers in Genetics, 2023)
Native chickens are dispersed in a wide range of geometry and they have influenced hereditary assets that are kept by farmers for various purposes. Mitochondrial DNA (mtDNA) is a widely utilized marker in the the molecular study because of its quick advancement, matrilineal legacy, and simple molecular structure. We performed NGS sequencing to investigate the mitochondrial genomes and to evaluate the hereditary connections, diversity, and measure of gene stream estimation in Indian native chicken breeds along with Red Jungle fowl. The chicken breeds were genotyped by using the D-loop region and 23 haplotypes were identified. In addition, when compared to only Indian native breeds, more haplotypes were identified in the NADH dehydrogenase subunits, Cytochrome c oxidase, Cytochrome b, ATP synthase subunit 6, and Ribosomal RNA genes. The phylogenetic examination indicated that the analyzed chicken breeds were divided into six significant clades: A, B, C, D, E, and F, and of which the F clad included Indian native breeds indicatinged the domestication of all Indian breeds in India. Additionally, our work affirmed that the Indian Red Jungle Fowl is the origin of reference Red Jungle Fowl as well as all Indian breeds, which is reflected in the dendrogram as well as network analysis based on the whole mtDNA and D-loop region. Albeit, Indian Red Jungle Fowl is distributed as an outgroup, proposing that this ancestry was reciprocally monophyletic. The mtDNA sequences of 2 Indian native chickens gave novel insights into adaptation mechanisms and the significance of important mtDNA variations in understanding the maternal lineages of native birds.